2017
DOI: 10.1071/rd17107
|View full text |Cite
|
Sign up to set email alerts
|

Delayed onset of puberty in male offspring from bisphenol A-treated dams is followed by the modulation of gene expression in the hypothalamic–pituitary–testis axis in adulthood

Abstract: Bisphenol A (BPA) is a synthetic endocrine-disrupting chemical of high prevalence in the environment, which may affect the function of the hypothalamic-pituitary-testis (HPT) axis in adult rats. The aim of the present study was to evaluate whether exposure to BPA during hypothalamic sexual differentiation at doses below the reproductive no observable adverse effect level of the World Health Organization causes changes in the regulation of the HPT axis. For this, 0.5 or 5mgkg BPA was injected subcutaneously to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Other rodent studies suggest that BPA exposure can affect T production with one report suggesting developmental exposure to BPA increases this hormone [84], whereas other studies suggest this chemical decreases T production [85; 86; 87; 88; 89]. Similar to the BPA-analogue studies reported above, BPA can also affect sperm production and quality and increase sperm DNA damage in rodent models [90; 91; 92; 93; 94].…”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 72%
“…Other rodent studies suggest that BPA exposure can affect T production with one report suggesting developmental exposure to BPA increases this hormone [84], whereas other studies suggest this chemical decreases T production [85; 86; 87; 88; 89]. Similar to the BPA-analogue studies reported above, BPA can also affect sperm production and quality and increase sperm DNA damage in rodent models [90; 91; 92; 93; 94].…”
Section: Neuroendocrine Disruption Due To Exposure Of Rodent Models Tmentioning
confidence: 72%
“…The activity of HPG axis in male rat offspring is affected by low BPA dose exposure from gestational day 18 to 5PND and causes delayed onset of puberty [162]. The expression rates of hypothalamic GnRH and esr2, pituitary FSH β subunit and AR, testicular FSH receptor and inhibin β subunit are increased in the adult exposed to low BPA doses (0.5 mg/kg), whereas serum T and LH levels are affected at higher doses (5 mg/kg) [162].…”
Section: Fig (3) the Targets Of Bpa Along The Hpg Axis And The Possible Interplay With Metabolic And Environmental Factors (A Higher Resomentioning
confidence: 99%
“…Endocrine disrupting chemicals (EDCs) might impact the production of various steroid and peptide hormones. For example, the classic EDC, BPA, can alter production of estrogen, testosterone, glucocorticoids, insulin, and likely other hormones (Akingbemi et al, 2004 ; Nakamura et al, 2010 ; Poimenova et al, 2010 ; Peretz et al, 2011 ; D'Cruz et al, 2012 ; Nanjappa et al, 2012 ; Castro et al, 2013 ; Garcia-Arevalo et al, 2016 ; Oliveira et al, 2017 ; Weldingh et al, 2017 ). Such EDC-induced endocrinopathies might be another mechanism by which host changes can influence the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%